KAJIAN KERENTANAN MASYARAKAT PESISIR TERHADAP DAMPAK PERUBAHAN IKLIM DI KABUPATEN LOMBOK BARAT DENGAN MENGGUNAKAN PENDEKATAN PARTISIPATIF - Andi Chairil Ichsan (Forestry Study Program University Of Mataram, 2018)
This study is an attempt to assess the vulnerability of coastal communities to climate change in a participatory way by assessing exposure, sensitivity and capacity of communities in ten coastal villages of western Lombok district in the face of various impacts climate change. The basic concept of the implementation of this study was constructed qualitatively, using a participatory approach. The method of study was adopted from the PRA (Participatory Rural Appraisal) method with adjustments to coastal and marine context contexts called Indonesian climath adaptation tools for coastal habitat (I-CATCH). he results of this study indicate that the villages that become the object of research have a middle and high degree of vulnerability. The complexity of the problems felt by the community due to changes in seasonal patterns that occur, especially on aspects of livelihood and social environment. On the other hand, the capacity of people in dealing with the symptoms and impacts of climate change that is quite extreme is still very limited. Local adaptation strategies are needed with a focus on two main aspects: capacity building and developing of disaster management activities.